Genomic profile, smoking, and response to anti-PD-1 therapy in non-small cell lung carcinoma. (2nd January 2016) - Hellmann, Matthew; Rizvi, Naiyer; Wolchok, Jedd D.; Chan, Timothy A.
ABSTRACT: The recent successes of immune checkpoint therapies have established a new era for the treatment of patients with cancer, yet the predictors of response remain largely undetermined. We recently demonstrated that the genomic landscape of lung cancers substantially influences the response to programmed cell death 1 receptor (PD-1) blockade, providing new insights into the molecular determinants of the response to immunotherapy.